retagged by
878 views

2 Answers

Best answer
3 votes
3 votes

We can write the number in the $ n^{\text{th}}$ group.

  • The number in $1^{\text{st}}$ group $ = (1)$
  • The number in $2^{\text{nd}}$ group $ = (2, 3, 4)$
  • The number in $3^{\text{rd}}$ group $ = (5, 6, 7, 8, 9)$
  • $\vdots \quad \vdots  \quad \vdots $
  • The number in $ n^{\text{th}}$ group $ = \left( n^{2} – (2n-2), n^{2} – (2n-1), \dots, n^{2} – 1, n^{2} \right)$

The number of element in $n^{\text{th}}$ group $ = 2n – 1$

So, the sum of numbers of $n^{\text{th}}$ group

$S_{n} = n^{2} + (n^{2}-1) + (n^{2}-2) + \dots + \left( n^{2} – (2n-2) \right)$

$\Rightarrow S_{n} = (2n – 1)n^{2} – \left( 1 + 2 + 3 + \dots + (2n-2) \right)$

$\Rightarrow S_{n}  = (2n-1)n^{2} + \frac{(2n-2)(2n-1)}{2}$

$\Rightarrow S_{n}  =  (2n-1)n^{2} + (n-1)(2n-1) $

$ \Rightarrow S_{n}  =  (2n-1)n^{2} + 2n^{2} – n – 2n + 1$

$\Rightarrow S_{n}  = (2n-1)n^{2} + 2n^{2} – 3n + 1$

$\Rightarrow S_{n}  = (2n-1) (n^{2} – n + 1) $

$\Rightarrow S_{n}  = 2n^{3} – 3n^{2} + 3n – 1 $

$\Rightarrow S_{n} = n^{3} + n^{3} – 3n^{2} + 3n – 1$

$\Rightarrow S_{n}  = n^{3} + (n-1)^{3} \quad [\because n^{3} – 3n^{2} + 3n – 1 = (n-1)^{3}]$

$\therefore$ The sum of the numbers in the $15^{\text{th}}$ group $ = 15^{3} + (15-1)^{3}$

$ \qquad \qquad \qquad = 15^{3} + 14^{3} = 3375 + 2744= 6119.$

Correct Answer $: \text{C}$

selected by
2 votes
2 votes
nth group starts with $(n-1)$$^{2}$ $+$ $1$ and ends with $n$$^{2}$ and every group consists $2n-1$ numbers
$15th$ group starts with 196 and ends with $225$

$sum$ = $\frac{No of terms}{2}$ * $[first$ $term$+$last$ $term]$ = $\frac{29}{2} * [(196+1) + 225]$ = $6119$
Answer:

Related questions

1 votes
1 votes
1 answer
1
soujanyareddy13 asked Jan 19, 2022
821 views
How many three-digit numbers are greater than $100$ and increase by $198$ when the three digits are arranged in the reverse order?